2022
DOI: 10.1021/acs.analchem.1c04762
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Pipeline of Rapid Isolation and Analysis of Human Plasma Exosomes for Cancer Discrimination Based on Deep Learning of MALDI-TOF MS Fingerprints

Abstract: Plasma exosomes have shown great potential for liquid biopsy in clinical cancer diagnosis. Herein, we present an integrated strategy for isolating and analyzing exosomes from human plasma rapidly and then discriminating different cancers excellently based on deep learning fingerprints of plasma exosomes. Sequential sizeexclusion chromatography (SSEC) was developed efficiently for separating exosomes from human plasma. SSEC isolated plasma exosomes, taking as less as 2 h for a single sample with high purity suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
(83 reference statements)
3
17
0
Order By: Relevance
“…S3 ). In summary, these results confirm work by others 14, 3139 that the size exclusion column methods of isolation yield pure EV for MASEV analysis in reasonable amounts of time.…”
Section: Resultssupporting
confidence: 89%
“…S3 ). In summary, these results confirm work by others 14, 3139 that the size exclusion column methods of isolation yield pure EV for MASEV analysis in reasonable amounts of time.…”
Section: Resultssupporting
confidence: 89%
“…Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been widely used to identify specific protein fingerprints associated with pathological changes in various diseases upon analysis of body fluids or tissue samples. MALDI-TOF MS has been recently applied to analyze TDEs for rapid diagnosis of melanoma, breast cancer, pancreatic cancer, early-stage lung cancer, and osteosarcoma [ 60 , [118] , [119] , [120] ]. MALDI-TOF MS spectra and SERS data of plasma EVs were used to discriminate TDEs of osteosarcoma patients from EVs of healthy controls for more accurate diagnosis of osteosarcoma [ 119 ].…”
Section: Advances In Tde Nucleic Acid and Protein Detectionmentioning
confidence: 99%
“…On the mature foundation of MALDI-TOF MS fingerprinting technology, many other samples have been used for biomarker discovery and cancer diagnosis, especially exosomes isolated from body fluids. , In 2019, Zhu et al used MALDI-TOF MS to analyze exosomes extracted from serum of melanoma patients and healthy donors and demonstrated that the mass fingerprinting of bloodstream-circulating exosomes can be used for cancer diagnosis and monitoring . In 2021, Han et al used MALDI-TOF MS to analyze serum exosomes from 12 healthy donors, 20 osteosarcoma patients without lung metastasis, and 20 osteosarcoma patients with lung metastasis.…”
Section: Clinical Application and Potential Of Maldi-tof Msmentioning
confidence: 99%